Regime Management at the Bottom of the Food Web - Gjelsvik Tiller, Rachel (The Journal of Environment & Development, 2010)
Fishing down the food chain is a controversial issue that demands further exploration. Redfeed is a marine species located on the second to last level on the food web. It is also one of the potential saviors of the aquaculture industry. The role of effective management of this species is of utmost importance to avoid the potential catastrophe associated with its overharvesting. Using a calculation of behavioral effectiveness, a blueprint redfeed regime is compared with the Convention for the Conservation of the Antarctic Marine Living Resources (CCAMLR), an ecosystem-based management regime with the now famous krill as its key species. Though the regimes are similar in nature, their geopolitical differences suggest that a future redfeed regime will be effective even though CCAMLR has not been. Ensuring that the redfeed is not merely incorporated into existing regimes, but is treated separately in an ecosystem-based regime, will alleviate the interplay this future redfeed regime otherwise would encounter.
Publisher: SAGE Publications Inc
Keywords: Antarktistraktaten; Sørishavet; fiskerier; internasjonal rett; krill; marin økologi; marine økosystemer; plankton; polarområdene

Distribution and demography of Antarctic krill in the Southeast Atlantic sector of the Southern Ocean during the austral summer 2008 - Krafft, Bjørn A.; Melle, W.; Knutsen, T.; Bagøien, E.; Broms, C.; Ellertsen, B.; Siegel, V. (Polar Biology, 2010)
This study documents horizontal distribution and demography of Antarctic krill (Euphausia superba) from the Southern Ocean during January–March 2008. The cruise predominantly occurred in CCAMLR Subarea 48.6, where knowledge about the ecosystem is limited. E. superba were not found north of 52°S. The biomass, estimated from trawl catches, was highest (63.09 g/m2) at a station 680 km southeast of Bouvetøya and at two stations 1,400 and 600 km southeast and southwest of Bouvetøya, 54.67 and 61.38 g/m2, respectively. Body length ranged from 19 to 61 mm (N = 8,538), with a mean of 42.0 ± 6.4 mm (SD). The overall sex ratio was 1:1, 46.2% males (13.2% adults and 33.0% subadults), 46.1% females (33.6% adults and 12.5% subadults), while 7.5% were juveniles. Trawl stations dominated by adults were found west and north of Bouvetøya. Stations with high proportions of subadults and juveniles were mainly found southeast of the island. Four cluster groups were differentiated: analyzing data on krill sex proportions, maturity stages, hydrography, nutrients and chlorophyll concentrations. Two groups represented stations located in the northern part of the study area, where E. superba were absent; water temperatures were higher and the nutrient concentrations lower compared to the groups where E. superba were present. This study shows that bathymetric features like the North Weddell Ridge including Bouvetøya are important for concentrating krill probably due to water mass characteristics and advective processes which influence regional krill demography. The southern regions of CCAMLR sector 48.6 are essential for understanding regional krill recruitment and production.
Keywords: Bouvetøya; Sørishavet; krill; marin biologi; marine økosystemer; zooplankton

The acoustic properties of Salpa thompsoni - Wiebe, Peter H.; Chu, Dezhang; Kaartvedt, Stein; Hundt, Anna; Melle, Webjorn; Ona, Egil; Batta-Lona, Paola (ICES Journal of Marine Science, 2010)
Wiebe, P. H., Chu, D., Kaartvedt, S., Hundt, A., Melle, W., Ona, E., and Batta-Lona, P. 2010. The acoustic properties of Salpa thompsoni. – ICES Journal of Marine Science, 67: 583–593.Aggregations of the salp Salpa thompsoni were encountered during the Antarctic krill and ecosystem-studies cruise on the RV “G.O. Sars” from 19 February to 27 March 2008. The salp's in situ target strength (TS), size, number of individuals in aggregate chains, and chain angle of orientation were determined. Shipboard measurements were made of Salpa thompsoni's material properties. Individual aggregates were mostly 45.5–60.6 mm in mean length; relatively rare solitaries were ∼100 mm. Chains ranged from 3 to at least 121 individuals, and in surface waters (<20 m), they showed no preferred angle of orientation. Sound-speed contrast (h) ranged from 1.0060 to 1.0201 and density contrast (g) estimates between 1.0000 and 1.0039. The in situ TS distributions peaked between −75 and −76 dB at 38 kHz, with a secondary peak at approximately −65 dB. TS ranged between −85 and −65 dB at 120 and 200 kHz and peaked around −74 dB. The measured in situ TS of salps reasonably matched the theoretical scattering-model predictions based on multi-individual chains. The backscattering from aggregate salps gives rise to TS values that can be similar to krill and other zooplankton with higher density and sound-speed contrasts.
Keywords: Bouvetøya; Sørishavet; copepoder; ekkolodd; krill; marin biologi; marine økosystemer; oseanografi; plankton